Nasa iyo na ang lahat a textual and historical analysis of the shifting images of masculinity of Daniel Padilla - Reyes, Robby Ligon 1993-
"This study looks into the image of masculinity and its possible shift/s, constructed by matinee idols in mainstream media. By looking into the images of masculinity represented and constructed by Daniel Padilla in his advertisements, music videos, movie roles, and television roles from 2011 up to present, this research analyzes and classifies his performed images of masculinity and locates points of shift. Guided by Easthope's masculine myth and Freud's constitutional bisexuality as the main analytical framework, supported by Butler's performativity, this research argues that Daniel Padilla, a matinee idol who should have a consistent onscreen image, portrayed and performed different images of masculinity over time of purposively chosen sample of media texts (i.e., TV commercials, music videos, movies, teleseryes) is done through semiotics in order to analyze the image of masculninity he portrayed in each material. The data and indicators are categorized based on Rolando Tolentino's categorization of bad boy - hegemonic masculinity- and good boy - subordinate masculinity. Finally, the element of time is included in the study in order to examine the changes in the resulting images of masculinity; to see the changes in Padilla's performance and his image of masculinity over time. Thus, analysis of the categorization is employed to locate the points of shift of images. The research then looks into the result to see if the categorization should only be limited to these two."